2021
DOI: 10.1029/2021gl095779
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Radiation Belts: The Energy‐Dependence of Self‐Limiting Electron Space Radiation

Abstract: Despite renewed recent attention, how the physical processes that are active in geospace combine to produce the observed dynamics of the Earth's electron radiation belts remains elusive (e.g., Li & Hudson, 2019; Millan & Thorne, 2007, and references therein). With increasing appreciation of disruptive or even potentially catastrophic impacts of this space radiation on an ever growing number of satellites (e.g., Baker, 2001;Baker et al., 1987;Reeves, 2007), the research area is also one of increasing societal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 36 publications
3
61
0
1
Order By: Relevance
“…Indeed, the theoretical Kennel-Petschek limit does not appear to change from storm to storm by more than a factor of approximately 2 across all energy channels. This result is consistent with that of Olifer et al (2021) where the superposed epoch analysis of the limiting flux shows that the Kennel-Petschek limit does not vary by more than a factor of 2 between the upper and lower quartiles within the ensemble of the 70 storms studied. This limit is controlled by the nature of the magnetized plasma and therefore, accordingly to our results, The black scatter plot shows the electron flux measurements, the blue line shows a fit of the relativistic kappa distribution to the spectra.…”
Section: Energy-dependent Flux Limit During Intense Stormssupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, the theoretical Kennel-Petschek limit does not appear to change from storm to storm by more than a factor of approximately 2 across all energy channels. This result is consistent with that of Olifer et al (2021) where the superposed epoch analysis of the limiting flux shows that the Kennel-Petschek limit does not vary by more than a factor of 2 between the upper and lower quartiles within the ensemble of the 70 storms studied. This limit is controlled by the nature of the magnetized plasma and therefore, accordingly to our results, The black scatter plot shows the electron flux measurements, the blue line shows a fit of the relativistic kappa distribution to the spectra.…”
Section: Energy-dependent Flux Limit During Intense Stormssupporting
confidence: 91%
“…A recent superposed epoch study by Olifer et al. (2021) has shown that electrons with energies below ∼850 keV are strongly affected by the presence of the Kennel‐Petschek limit during geomagnetic storms. The results from Olifer et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on superposed epoch analysis of 70 geomagnetic storms, the study of Olifer et al. (2021) revealed consistency of the upper limit of electron fluxes with energies <∼850 keV between the observations and the theoretical results from KP theory. However, the upper limit of MeV electron fluxes is not well captured by KP theory in either Olifer et al.…”
Section: Introductionmentioning
confidence: 85%
“…However, the upper limit of MeV electron fluxes is not well captured by KP theory in either Olifer et al. (2021) or Zhang et al. (2021), since the electron fluxes at such high energies typically do not result in wave growth, and this high energy upper flux limit still remains not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…For different energy channels, the loss at L* = 5.5 is ∼30 times larger than at L* = 4.0 reaching values as large as ∼100 for the highest energies. The magnitude of this loss during low LCDS events is approximately an order of magnitude more intense than has been reported in some previous superposed epoch studies (Morley et al, 2010;Murphy et al, 2018;Olifer et al, 2021;Turner et al, 2019). Second, the fractional loss is very clearly much more significant at higher energies.…”
Section: Similarity and Repeatability Of The Radiation Belt Lossmentioning
confidence: 53%